2003
DOI: 10.1002/jgm.377
|View full text |Cite
|
Sign up to set email alerts
|

Aspartylglucosaminidase (AGA) is efficiently produced and endocytosed by glial cells: implication for the therapy of a lysosomal storage disorder

Abstract: These data indicate the importance of glial cells in the expression and transport of AGA. Subsequently, new approaches can be developed for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Interestingly, the AGA promoter was shown to be a very powerful promoter in glia [20]. In the in vitro studies the glial cells showed much higher expression, exocytosing and endocytosing capacity of AGA than neurons.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly, the AGA promoter was shown to be a very powerful promoter in glia [20]. In the in vitro studies the glial cells showed much higher expression, exocytosing and endocytosing capacity of AGA than neurons.…”
Section: Discussionmentioning
confidence: 98%
“…The sections were fixed in 4% PFA for 15 min, washed three times with PBS, blocked and permeabilized in 0.5% bovine serum albumin (BSA) and 0.2% saponin buffer. Double stainings were performed using a rabbit anti-human AGA at 1 : 200 dilution [2,10,16] and rat Lamp-1 at 1 : 50 dilution (ID4B), mouse NeuN at 1 : 100 dilution or pGFAP at a 1 : 200 dilution as primary antibodies [20]. Corresponding secondary antibodies were goat anti-rabbit rhodamine (TRITC) and goat anti-rat/mouse/rabbit fluorescein (FITC) (Jackson Immunoresearch).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, human AGA promoter was found to be a very powerful glia promoter. 3 We have also used adenovirus for overexpression of AGA in vivo in AGU mouse brain resulting in partial correction of brain pathology. 4 The AGU mouse model presents tissue pathology similar to humans including lysosomal storage in all tissues.…”
mentioning
confidence: 99%